Study fenomenologi: Intervensi Sosial Untuk Mereduksi Stigma Terhadap WUS Dalam Memutus Mata Rantai Penularan Covid-19 - Surbakti, Elisabeth; Maida Pardosi; Efendi Sianturi; Rina Doriana Pasaribu; Efbertias Sitorus (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2024)
Social stigma can encourage people to hide their illness so that they are not discriminated against, prevent them from seeking medical assistance immediately, and prevent them from carrying out healthy lifestyle behaviors without realizing it will cause more transmission to others. The aim of the study was to carry out a phenomenological survey of social interventions to reduce the stigma against WUS in breaking the chain of transmission of Covid-19 in the working area of the Medan Helvetia Health Center. The target to be achieved from this research is the formation of cooperation in tackling the transmission of Covid-19 which involves all community leaders, especially WUS. The research was carried out in Helvetia District, the working area of the Helvetia Health Center, Medan City. The research method was carried out using a qualitative approach. The qualitative approach used is participatory action research. The research procedures to be carried out are engagement/intake, data collection and need assessment (phenomenological survey), model formulation, intervention and monitoring and evaluation and termination. Data collection methods were carried out by sharing, in-depth interviews, (FGD) and questionnaires. Interactive model analysis is used to analyze qualitative data on phenomenological surveys and the process of conducting participatory action research. The results of the research, the phenomenological survey generally closed oneself when exposed to Covid-19, did not tell neighbors, friends or family but after recovering they were told, with the aim of not being ostracized or avoided by the local community. The FGD was conducted to look at the problems found in the phenomenological survey, and the results of the discussion resulted in a social intervention, namely the training of the Covid-19 Task Force as counselees in reducing the stigma of Covid-19, carried out for 3 days. Implementation of participatory action research requires a long time to be able to see changes in behavior and social change, for this reason further research is needed to see the persistence of interventions carried out by the Covid-19 Task Force.